2020
DOI: 10.14309/ctg.0000000000000177
|View full text |Cite
|
Sign up to set email alerts
|

Infliximab Originator, Infliximab Biosimilar, and Adalimumab Are More Effective in Crohn's Disease Than Ulcerative Colitis: A Real-Life Cohort Study

Abstract: INTRODUCTION: There are no real-life studies comparing the efficacy and safety of the different antitumor necrosis factor (TNF)-α drugs available in patients with ulcerative colitis (UC) and Crohn's disease (CD). To verify the effectiveness and tolerability of different anti–TNF-α agents (infliximab [IFX] originator, biosimilar CTP13, and adalimumab [ADA]) in patients with moderate-to-severe CD and UC. METHODS: Retrospectively, patients with moderate-to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…In fact, a recent study, comparing efficacy and safety of different anti-TNF-α between patients with moderate-to-severe UC and CD, demonstrated a better clinical response to anti-TNF-α treatment, including ADA originator, in patients with CD. 13 …”
Section: Discussionmentioning
confidence: 99%
“…In fact, a recent study, comparing efficacy and safety of different anti-TNF-α between patients with moderate-to-severe UC and CD, demonstrated a better clinical response to anti-TNF-α treatment, including ADA originator, in patients with CD. 13 …”
Section: Discussionmentioning
confidence: 99%
“…and halt disease progression 7,8 . Among these agents, Adalimumab (ADA) originator, Humira, a fully human IgG1 monoclonal antibody directed against TNF-α, was introduced in 2002 and soon became one of the mainstays of therapy for moderate to severe IBD 7,[9][10][11] .…”
mentioning
confidence: 99%
“…However, a previous study from our research group comparing the effectiveness and safety of Infliximab originator, CT-P13 and Adalimumab between patients with CD and UC showed that, at T2, 31.1% of ADA, 16.7% of IFX originator, and 36.2% of CT-P13 biosimilar patients needed treatment optimization. 36 In addition, at T2, 17 out of 76 (22.3%) patients had a recurrence of the disease. Surely, we do not know whether this failure was related to the switch to SB2 biosimilar or might be secondary to the physiologic loss of response recorded with this type of drug and already reported in the medical literature (i.e.…”
Section: Discussionmentioning
confidence: 96%